Xenophon - Atack, Carol ca. 20./21. Jh (Classical Association, 2024)
"Xenophon of Athens wrote on a variety of subjects, ranging across history and politics (Hellenica, Constitution of the Spartans), biography (Cyropaedia, Agesilaus), leadership and economic advice (Poroi, Hipparchicus, Cynegeticus), memoirs of his own activities (Anabasis) and philosophical dialogue (Hiero), often drawing on his experience of Socrates (Apology, Memorabilia, Oeconomicus, Symposium). This book explores the coherent worldview which underlies these apparently disparate works, starting with his account of the household and moving out through city and army to large-scale imperial power, always framed by his respect for the divine ordering of the cosmos and featuring his distinctive and lively prose style. This book also places Xenophon's thought in its historical context, evaluating how he responded to the work of predecessors and contemporaries, both historians like Thucydides and philosophers like Plato and the other followers of Socrates, making him an important witness to the intellectual life of fourth-century BCE Greece."
Keywords: Xenophon -- v430-v354